Employee Motivation in Light Oncial, Non-Financial Rewards and Employee Commitment among Pharmaceutical SMEs of Indonesia - Matloob, Sheema; Shah, Saeed Abbas; Shah, Muzafar Hussain (The Economics and Finance Letters, 2021)
This paper aim to assess the effect of financial and non-financial rewards on employees’ motivation along with mediating effect of employee’s commitment on relationship of financial and non-financial rewards with employees’ motivation in pharmaceutical industry of Indonesia. For achieving the purpose, structural equation modeling was performed on collected data from 235 employees through self-administered questionnaires from pharmaceutical industry in Indonesia. This research found significant and positive effect of non-financial payments with employee motivation in results of direct relationship, current study found positive but insignificant effect of financial rewards on motivation during direct relationship. This study also found significant results of effect of financial and non-financial rewards on employee commitment. Furthermore current study found positive significant results during mediation by employees’ commitment between financial rewards, non-financial rewards with motivation, and employee commitment proved as good mediator. Implication and recommendations were also discussed in current research.